2007
DOI: 10.1007/s12094-007-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of liver metastases from colorectal carcinoma in elderly patients. When is it worthwhile?

Abstract: The elderly have a higher mortality. In recent years that difference has been markedly reduced. Excluding the postoperative mortality, the overall survival and disease-free survival are similar between both groups. The criteria to indicate surgery must be the same in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 27 publications
4
59
1
Order By: Relevance
“…Nevertheless, the safety of extended hepatic resections in elderly patients is unclear, and some authors have reported higher postoperative mortality rates related to agedassociated co-morbidities [18,19]. No experimental studies have globally analyzed the effect of age on oxidative/nitrosative stress, cytokine profile, and liver regeneration after extended liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the safety of extended hepatic resections in elderly patients is unclear, and some authors have reported higher postoperative mortality rates related to agedassociated co-morbidities [18,19]. No experimental studies have globally analyzed the effect of age on oxidative/nitrosative stress, cytokine profile, and liver regeneration after extended liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…In the HORG-FOLFOXIRI trial, no different clinical outcome was observed in elderly versus non-elderly patients; significantly lower clinical outcome was reported in patients with PS 2 [31, 32]. Liver metastasectomies were reported in 1.3% and 4.4% patients in FOLFIRI and FOLFOXIRI arms, respectively [32] and can achieve OS 43 months, not significantly different from younger patients in the experience of liver resection in elderly patients [35]. Morbidity and/or mortality after liver surgery were significantly higher in elderly patients (8%) [36].…”
Section: Discussionmentioning
confidence: 99%
“…A complex decision-making process discriminating patients’ fitness, and tailoring a personalized medical treatment, is challenging: patients unfit for FIr-B/FOx can be treated with a two-drug first line combination regimen (31), but showed worse clinical outcome. No increased morbidity, nor mortality was reported in unfit patients who underwent secondary liver metastasectomies, reported as significantly higher in elderly patients (8%) (48). …”
Section: Discussionmentioning
confidence: 99%